Synthesis of a Large, Shape-Flexible, Solvatomorphic Porous Organic Cage - Teng, Baiyang; Little, Marc A; Hasell, Tom; Chong, Samantha Y; Jelfs, Kim E; Clowes, Rob; Briggs, Michael E; Cooper, Andrew I (Crystal growth & design, 2019)
Porous organic cages have emerged over the last 10 years as a subclass of functional microporous materials. However, among all of the organic cages reported, large multicomponent organic cages with 20 components or more are still rare. Here, we present an [8 + 12] porous organic imine cage, CC20, which has an apparent surface area up to 1752 m2 g–1, depending on the crystallization and activation conditions. The cage is solvatomorphic and displays distinct geometrical cage structures, caused by crystal-packing effects, in its crystal structures. This indicates that larger cages can display a certain range of shape flexibility in the solid state, while remaining shape persistent and porous.